Capacity optimization of grid connected solar/fuel cell energy system using hybrid ABC-PSO algorithm - Singh, Shakti; Chauhan, Prachi; Singh, NirbhowJap (International journal of hydrogen energy, 2020)
Hybrid renewable based power generation has emerged as a major breakthrough in electrical power system due to their capability of providing competitive and carbon free electricity to the consumer. This paper presents techno-economic analysis of a grid connected solar photovoltaic-fuel cell based hybrid energy system to supply the electrical load demands of a small shopping complex located at the University campus in India. The proposed system has been designed by considering the cost of energy purchase and sold to the utility grid and further ensuring the smooth power flow management between elements of the system and the utility grid. A simplified mathematical modeling of the proposed hybrid energy system, including power and hydrogen management has been presented to access the potential of hydrogen based energy systems. Component sizing to optimize the net present cost of the proposed system has been performed employing three meta-heuristic algorithms, i.e., artificial bee colony, particle swarm optimization and a hybrid of both. The experimental results obtained from three algorithms have been compared in terms of cost effectiveness of the system. The hybrid system has been designed to cater the total electricity demand of 135 MWh/yr of a small community center. It has emerged from the simulation results that the total electricity demand could be met with a 106 kW solar photovoltaic, 8 kW fuel cell, 45 kW electrolyzer and a 150 kg of hydrogen tank. The proposed grid connected system has 30 kW grid purchase and 25 kW grid sale capacities, respectively. In this paper, grid sale and purchase capacities have been considered as a decision variable along with other system component sizing. Loss of power supply probability is minimized along with objective function i.e., levelized cost of electricity (LCOE) using the exterior penalty method. It is evident from the results that the proposed system is economically viable with a LCOE of 0.104 $/kWh. It has emerged from the results that the proposed hybrid energy system may be helpful to promote hydrogen and solar based energy system to reduce the reliance on the overburden grid, particularly, in developing countries.